Chitosan-based microparticles for immobilization of TiO2 nanoparticles and their application for photodegradation of textile dyes. (September 2016) - Lučić Škorić, Marija; Terzić, Ivan; Milosavljević, Nedeljko; Radetić, Maja; Šaponjić, Zoran; Radoičić, Marija; Kalagasidis Krušić, Melina
Graphical abstract: Highlights: Novel chitosan microparticles were synthetized by inverse suspension polymerization. Freshly synthetized TiO2 NPs were successfully immobilized onto microparticles. TiO2 NPs successfully photodegraded various azo dyes. Excellent photocatalytic activity is maintained after three repeated cycles. Abstract: The present paper deals with removal and photocatalytic degradation of the textile dyes by TiO2 nanoparticles immobilized onto chitosan-based microparticles. The microparticles composed of chitosan (Ch) and poly(methacrylic acid) (PMA) were fabricated for the first time by inverse suspension polymerization. They were utilized for colloidal TiO2 nanoparticles immobilization, synthetized by acidic hydrolysis of TiCl4 . To evaluate the potential application of Ch/PMA/TiO2 microparticles for treatment of textile wastwaters, their photocatalytic activity was examined by degradation assessment of three different groups of anionic azo dyes in aqueous solutions under solar light simulating source. FTIR analysis revealed that Ch and PMA were incorporated in the polymer network. SEM and optical microscopy confirmed their spherical shape. Under illumination, Ch/PMA/TiO2 microparticles completely removed dyes C.I. Acid Orange 7, C.I. Acid Red 18, C.I. Acid Blue 113, C.I. Reactive Black 5, C.I. Direct Blue 78, while removal degree of C.I. Reactive Yellow 17 was 75%. It was found that pH had significant influence on the photocatalytic activity of Ch/PMA/TiO2 microparticles. Increase of solution pH from acidic to alkaline, lead to decrease in photodegradation rate of C.I. Acid Orange 7 during the first hours of illumination. After three illumination cycles, removal degree of C.I. Acid Orange 7 was maintained at remarkably high level (95% at pH 5.60 and 100% at pH 2.00 and 8.00), indicating that microparticles could be reused without significant loss of photocatalytic efficiency.